S86 The Inflammatory Response To Streptococcus Pneumoniae Is Exaggerated By The Polysaccharide Capsule. (10th November 2014) - Periselneris, JN; Chimalapati, S; Tomlinson, G; Dyson, A; Hyams, C; Rukke, H; Peterson, F; Singer, M; Noursadeghi, M; Brown, JS
Abstract : Streptococcus pneumoniae infections characteristically cause a high degree of inflammation. The S. pneumoniae polysaccharide capsule prevents opsonophagocytosis and is essential for virulence. The capsule might also be expected to reduce the host's inflammatory response by inhibiting bacterial interactions with pro-inflammatory signalling proteins eg toll-like receptors (TLR), but this has not previously been investigated. Using isogenic unencapsulated strains and in vitro and in vivo models of infection we have characterised capsule effects on the inflammatory response to S. pneumoniae. Surprisingly, although the unencapsulated (Δ cps ) S. pneumoniae strain was much more sensitive to phagocytosis by macrophages and induced a stronger NFκB response by human monocyte derived macrophages (MDMs) it caused similar levels of stimulation of a TLR2 reporter cell line as the encapsulated strain TIGR4. In addition, microarrays demonstrated increased transcription of pro-inflammatory cytokines by MDMs in response to TIGR4 compared to the Δ cps strain, and quantitative PCR and ELISAs confirmed stronger TNF, IL1β, and IL6 responses by MDMs to TIGR4. Furthermore, compared to the Δ cps strain the TIGR4 strain caused greater neutrophil recruitment and higher cytokine levels in the lungs in a mouse model of pneumonia, as well as higher serum cytokine levels with worse hypotension in a rat model of sepsis. Additional in vitro experiments excluded antibody, complement, pneumolysin, the inflammasome, and lectin-mediated signalling as mechanisms driving differences in inflammatory responses between TIGR4 and Δ cps . Expression of the TIGR4 capsule in Streptococcus mitis did not increase MDM or murine inflammatory responses. Notably, preventing phagocytosis with cytochalasin D did not alter differences in the inflammatory response between TIGR4 and the Δ cps strains, and in silico analysis suggested the Δ cps strain activated a wider range of transcription factors. Overall, the data indicate that unencapsulated S. pneumoniae stimulate a wider range of host cell signalling pathways than encapsulated bacteria, some of which are likely to be anti-inflammatory. Hence the capsule, rather than reducing inflammation, causes increased pro-inflammatory responses and subsequent disturbances to host physiology during S. pneumoniae infection. Targeting the mechanisms responsible for capsule-dependent inflammation could offer novel treatment options for reducing the morbidity and mortality associated with S. pneumoniae infections.